Uprooting racism : how white people can work for racial justice - Kivel, Paul (New Society Publishers, 2017)
"There's a long tradition of white people opposing racism--but there are also many excuses we give for not getting involved. Now in a fully updated 4th edition, Uprooting Racism is the supportive, practical go-to guide for helping white people work with others for equal opportunity, democracy, and justice in these divisive and angry times."--